Prospective Randomized Control Study on the Efficiency and Safety of a Novel Port-site Closure Device, the EZ-close Port-site Closure System. Issue 5 (October 2019) - Kim, Hee Youn; Lee, Seung-Ju
Abstract : Aim: The efficiency and safety of EZ-close Port-Site Closure System were investigated in comparison with those of the Carter-Thomason CloseSure System (CT) device. Methods: This was a prospective randomized control study. The primary outcome was the time taken to complete the closure of the port site using either the EZ or CT. The suture time (mean±SD) for the EZ group was significantly less than that of the CT group (36.8±10.1 s for the EZ group vs. 48.9±21.5 s for the CT group, P =0.004). There was no need for additional instruments in the EZ group, but in 84.6% of the patients in the CT group, a grasper was required to hold the tie ( P <0.05). There was no difference in the complication rates between the 2 groups. Conclusions: The EZ device showed an improved efficiency and similar safety compared with that of the CT device. Its main advantage lied in enabling the surgeon to be totally self-sufficient for the whole port-site closing procedure.